The Witness, the Silenced, and the Rebel—Women in Search of Their Voice: Female Characters in Brian Friel’s Translations and Anne Devlin’s Ourselves Alone - Kvéder, Bence Gábor (FOCUS: Papers in English Literary and Cultural Studies, 2018)
It appears to have become a commonplace of Irish literary criticism that in Translations (1980) Brian Friel dramatizes largely national and historical issues. Referred to as his “most obviously postcolonial play” (Bertha 158), it is known for having the “nineteenth-century plot and setting [that] bore on Anglo-Irish relations in the present” (Roche, Theatre and Politics 2). Raising communal awareness, the play concentrates on the “key transitional moment when Irish gave way to English, when a culture was forced to translate itself into a different linguistic landscape” (Pelletier 68). In such a collectively damaging situation, personal problems could easily be overlooked. However, Ondřej Pilný emphasizes that Friel in general was “interested predominantly in individual people and their emotions, in their micro-narratives and their position within the surrounding discourse” (113). Whereas the hardships and traumas depicted in Translations, and especially their consequences, are suffered by the characters as members of a community in the first place, this does not necessarily mean that personal issues are missing from the drama.